ANALISIS KEPUTUSAN RUSIA DALAM MENERIMA TEKNOLOGI 5G HUAWEI TECHNOLOGIES CO., LTD. PADA TAHUN 2019 - Verko, Weinton; Kumala Dewi, Putu Ratih; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 02 (2022): Jurnal DIKSHI, 2022)
This research aims to describe the rationality of the Russian Government’s decision to accept 5G technology from Huawei in 2019. The enforcement of sanctions towards Huawei's 5G technology in May 2019 led Huawei shift a number of investments and cooperation, including to Russia. Russian Government has decided to accept Huawei's 5G technology development cooperation even if there are domestic warnings of security threats from Huawei. The researcher uses the concept of digital economy and rational actor model to analyze the rationality of Huawei’s 5G Technology cooperation acceptance decision. This research examines that Russian Government's decision to accept Huawei's 5G technology cooperation is determined through a value-maximizing process by calculating the costs and benefits. The Russian Government puts the Huawei's 5G technology development cooperation as a driver for the development of the country's 5G technology infrastructure that can help implement of Russia's Digital Economy Program.   Keywords: Digital Economy, Huawei’s 5G Technology, Rationality, Russia